Winning STEM innovation through entrepreneurship: a case study / Nur Azimah Idris, Noor Azizah Mazeni and Mohd Syafiq Abdul Rahman - Idris, Nur Azimah; Mazeni, Noor Azizah; Abdul Rahman, Mohd Syafiq (Unit Penerbitan JSKM, 2025)
STEM competitions serve as a platform for students to apply scientific and technological knowledge in real-world problem-solving. This study examines the key success factors of a winning STEM innovation, focusing on a secondary school team that developed Carissa Carandas Natural Lip Balm. The team won gold medals at the Bangkok International Intellectual Property, Invention, Innovation and Technology Exposition (IPITEx) 2025 in Thailand and the Malaysia Technology Expo (MTE) 2025, two of the most prestigious innovation exhibitions in their respective countries. Through a qualitative case study approach, this research analyzes the innovation process, challenges faced, and the impact of mentorship and commercialization strategies. Findings indicate that a combination of scientific research, entrepreneurial integration, and strong mentorship from school and university-level experts significantly contributed to their success. A key distinguishing factor was the team’s decision to sell their product at both exhibitions, proving its market readiness and commercial viability. The study highlights the importance of integrating entrepreneurial elements into STEM education, providing students with both technical expertise and business acumen. These findings offer valuable insights for educators, competition organizers, and policymakers in enhancing STEM innovation frameworks.